THE INFLUENCE OF HARDWARE AND TECHNOLOGICAL FACTORS ON THE PROCESS OF SHRINKAGE DURING COOLING OF BAKERY PRODUCTS - Victor Alexandrovich Balyubash; Artyom Sergeevich Pastukhov; Sergey Evgenevich Alyoshichev; Evgenia Alexandrovna Travina (Современная наука и инновации)
The article considers the influence of the heat capacity of bakery products during the cooling of a freshly baked loaf of bread to 35 °C. The calculations carried out using the previously developed by authors computer system have shown that conducting the cooling process taking into account, the thermophysical properties of the cooled products makes it possible to increase energy efficiency and increase the efficiency of the cooling process by 30%.